Radiotherapy in Prostate Cancer Innovative Techniques and Current Controversies - Geinitz, Hans.; Geinitz, Hans.; Roach III, Mack.; Roach III, Mack.; van As, Nicholas.; van As, Nicholas. (Radiation Oncology, 2015)
Radiation treatment is rapidly evolving owing to the coordinated research of physicists, engineers, computer and imaging specialists, and physicians. Today, the arsenal of “high-precision” or “targeted” radiotherapy includes multimodal imaging, in vivo dosimetry, Monte Carlo techniques for dose planning, patient immobilization techniques, intensity-modulated radiotherapy (IMRT), image-guided radiotherapy (IGRT), biologically adapted radiotherapy (BART), quality assurance methods, novel methods of brachytherapy, and, at the far end of the scale, particle beam radiotherapy using protons and carbon ions. These approaches are like pieces of a puzzle that need to be put together to provide the prostate cancer patient with high-level optimized radiation treatment. This book examines in detail the role of the above-mentioned innovative radiation techniques in the management of prostate cancer. In addition, a variety of current controversies regarding treatment are carefully explored, including whether prophylactic treatment of the pelvic lymphatics is essential, the magnitude of the effect of dose escalation, whether a benefit accrues from hypofractionation, and what evidence exists for the superiority of protons or heavy ions. Radiotherapy in Prostate Cancer: Innovative Techniques and Current Controversies is intended for both radiation oncologists and urologists with an interest in the up-to-date capabilities of modern radiation oncology for the treatment of prostate cancer.